Predictors of shoulder injuries in female collegiate swimmers - Lippincott, E. L.; Hellman, M. A.; Michener, L. A.; Shaw K. (Journal of Athletic Training, 2019)
Context: As many as 90% of competitive swimmers will experience shoulder pain at some point in their career. Shoulder impairments and swim history, occurring singularly or in combination, may be risk factors for shoulder injury. The objective of this study was to determine if shoulder impairments and swim history are risk factors for shoulder injury in female collegiate swimmers. Methods: Study design and setting: prospective longitudinal cohort, multi-center collegiate teams. Patient population: Female collegiate swimmers from four NCAA Division II universities (n=53 swimmers/106 shoulders, mean age=19.3 +/- 1.2 yrs). Intervention: All participants provided consent and completed a preseason demographic and swimming-related questionnaire and underwent musculoskeletal impairment measures. Information gathered from the questionnaire included the participant`s swim history (eg, age when starting competitive swimming, preferred swim stroke and distance) and shoulder injury history. Shoulder impairment measurements included scapular dyskinesis, glenohumeral range of motion and laxity, pecto-ralis minor length, and shoulder muscle strength and endurance. Shoulder injury data was collected over a 16-week season. A shoulder injury was defined as swimming-related shoulder pain that required medical attention and resulted in at least one modified or missed athlete exposure. Statistical analysis: Mann-Whitney U and Chi square tests were used to determine differences in preseason shoulder impairments and swim characteristics between swimmers who did and did not develop a shoulder injury. Impairments found to be significant were entered into a logistic regression to determine their ability to predict shoulder injury during the season. A priori significance was set at 0.05. Results: Fourteen new shoulder injuries were reported during the season. No differences were noted in preseason shoulder impairments between swimmers who did and did not develop shoulder pain. An injury was reported in 7 of the 18 shoulders with a history of shoulder pain, compared to 7 of the 88 shoulders with no history of shoulder pain (p=0.002). Previous shoulder injury was the sole predictor of an in-season shoulder injury (B=7.4; p=0.001; 95% CI 2.17, 25.00). Conclusions: Swimmers who sustained an injury during the season did not display any differences in pre-season shoulder impairments or swim characteristics, when compared to those swimmers who did not develop a shoulder injury. Swimming history did differentiate those who developed an injury. Swimmers with a history of shoulder injury are 7 times more likely to develop an in-season shoulder injury compared those without a history of shoulder injury. These results are similar to previous injury surveillance research that indicates previous injury is often a predictor of future injury. Limitations include the small number of new injuries and the measurement strategies for shoulder muscle endurance. Future research should include a larger sample size and further investigate shoulder impairments in swimmers with a history of shoulder pain.